The impact of implementing electronic education through the Madrasati platform and its relationship to the level of job satisfaction among teachers in the Mecca region - Alotaibi, Badriah Mohammad (Journal of Economic, Administrative and Legal Sciences, 2024)
The current study aimed to determine the level of job satisfaction among teachers in the Mecca region and to investigate the impact of implementing electronic education through the Madrasati platform on the job satisfaction of teachers in the Mecca region. A descriptive survey method was used, through a questionnaire distributed to a sample of 200 male and female teachers. The results showed a high level of job satisfaction among the teachers, in addition to a positive relationship between the use of electronic education through the Madrasati platform and the level of job satisfaction among teachers. In light of its findings, the study recommended conducting an initial survey of teachers to understand the extent of use of e-learning and the Madrasati platform and measure their current level of job satisfaction, analysing quantitative data on the use of e-learning and the Madrasati platform by teachers and correlating it with their level of job satisfaction, conducting interviews and discussions with a sample of teachers to understand their personal experiences with e-learning, and recommended providing guidelines for developing e-learning programmes to improve teachers' satisfaction and enhance their experience.
Keywords: Electronic education; job satisfaction; Madrasati platform; teachers